2006
DOI: 10.1111/j.1600-0897.2005.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cells: Similarities and Differences Between Human and Murine Embryonic Stem Cells

Abstract: The derivation of murine embryonic stem (mES) cell lines was reported for the first time in 1981 (Nature, 1981; 292:154-156; Proc Natl Acad Sci U S A, 1981; 78:7634-7638), and they have since proved to be a very useful tool with which to study mammalian development, which is characterized by pluripotency and differentiation. About 20 years later, the successful generation of human embryonic stem (hES) cell lines was described (Science, 1998; 282:1145-1147). Although mES and hES are derived from mammals, they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 52 publications
1
39
1
1
Order By: Relevance
“…The transcription factor oct3/4 is expressed in ES cells but switched off permanently soon after differentiation has begun (Koestenbauer et al 2006). In 2D FISH experiments using air-dried nuclei, the oct3/4 gene was described in human lymphoblastoid cells as being on average 0.03 μm inside the boundary of its chromosome territory but 0.15 μm outside in human ES cells and thus most likely outside of the territory in a majority of ES cell nuclei (Wiblin et al 2005).…”
Section: Gene Positioning and Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factor oct3/4 is expressed in ES cells but switched off permanently soon after differentiation has begun (Koestenbauer et al 2006). In 2D FISH experiments using air-dried nuclei, the oct3/4 gene was described in human lymphoblastoid cells as being on average 0.03 μm inside the boundary of its chromosome territory but 0.15 μm outside in human ES cells and thus most likely outside of the territory in a majority of ES cell nuclei (Wiblin et al 2005).…”
Section: Gene Positioning and Expressionmentioning
confidence: 99%
“…However, in both cell types, the distribution of distances from oct3/4 locus signals matched the one from the territory itself rather closely. The reason for the differences described for mouse and human oct3/4 locus positioning relative to their territory may lay in a different expression of neighboring major histocompatibility complex class I region genes (see Wiblin et al 2005 for references) or other differences between human and murine ES cells (Koestenbauer et al 2006). …”
Section: Gene Positioning and Expressionmentioning
confidence: 99%
“…In particular, several studies have shown that applying cyclic strain/stretch to mouse and human ESCs grown on elastic substrates can modify fate decisions in different directions (Saha et al, 2006;Schmelter et al, 2006;Gwak et al, 2008;Shimizu et al, 2008;Heo & Lee, 2011;Wan et al, 2011;Horiuchi et al, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 2012; Teramura et al, 2012). Furthermore, although mouse and human ESCs share the same core transcription factor networks for self-renewal and pluripotency (Smith 2001;Rao 2004;Van Hoof et al, 2006;Koestenbauer et al, 2006) they differ substantially in their growth requirements, and in particular, the mechanical interactions required to maintain their functions and viability (Ginis et al, 2004;Sato et a., 2003;Hayashi et al, 2007;Chowdhury et al, 2010;Xu et al, 2010). It remains to be determined whether they also differ in the molecules and mechanisms that sense and transduce different mechanical cues into specific responses.…”
Section: Manuscriptmentioning
confidence: 99%
“…The ICM consists of primitive ectoderm cells, which subsequently develop into epiblast cells in postimplantation embryos. Despite these ontogenic similarities human and murine ESC do not resemble each other in many aspects [9]. For example, murine ESC rely on leukemia inhibitory factor (LIF) and bone morphogenic protein-4 (BMP4) for maintenance of pluripotency [10,11], whilst human ESC are dependent on TGFβ/Activin/Nodal pathway activity and fibroblast growth factor-2 (FGF2) [12][13][14][15][16][17] and thus resemble epiblast stem cells (EpiSC).…”
mentioning
confidence: 99%